The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0102-33062004000200007
|View full text |Cite
|
Sign up to set email alerts
|

Análise florística das pteridófitas do Parque Nacional da Restinga de Jurubatiba, Rio de Janeiro, Brasil

Abstract: RESUMO -(Análise florística das pteridófitas do Parque Nacional da Restinga de Jurubatiba, Rio de Janeiro, Brasil). O Parque Nacional da Restinga de Jurubatiba, localizado no norte do Estado do Rio de Janeiro, abrange os municípios de Macaé, Carapebus e Quissamã. Foram registradas para a área de estudo 12 famílias com 21 gêneros e 32 espécies. As famílias encontradas foram Blechnaceae, Cyatheaceae, Davalliaceae, Dennstaedtiaceae, Dryopteridaceae, Gleicheniaceae, Lycopodiaceae, Polypodiaceae, Pteridaceae, Salvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 10 publications
2
9
0
13
Order By: Relevance
“…Most floristic studies on coastal ferns have been restricted to vegetation fragments, parks, conservation units or some specific synusiae (Behar & Viégas 1992;Labiak & Prado 1998;Kersten & Silva 2001;Santos et al 2004;Dittrich et al 2005;Athayde Filho & Windisch 2006;Gonzatti et al 2014b). Despite having an extensive survey area, the richness observed in the present study is lower than that found by other authors in smaller tropical rain and Araucaria forest areas (Mynssen & Windisch 2004;Schwartsburd & Labiak 2007;Salino & Almeida 2008;Prado & Labiak 2009;Gasper & Sevegnani 2010;Souza et al 2012), all of which were in lower latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Most floristic studies on coastal ferns have been restricted to vegetation fragments, parks, conservation units or some specific synusiae (Behar & Viégas 1992;Labiak & Prado 1998;Kersten & Silva 2001;Santos et al 2004;Dittrich et al 2005;Athayde Filho & Windisch 2006;Gonzatti et al 2014b). Despite having an extensive survey area, the richness observed in the present study is lower than that found by other authors in smaller tropical rain and Araucaria forest areas (Mynssen & Windisch 2004;Schwartsburd & Labiak 2007;Salino & Almeida 2008;Prado & Labiak 2009;Gasper & Sevegnani 2010;Souza et al 2012), all of which were in lower latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…2) (Ferrazo et al 2008) and the herbaceous-swampy formation of the Jurubatiba Coastal Woodlands National Park (Rio de Janeiro State) (Santos et al 2004) (Neves & Bauermann 2003;Medeanic, 2006). Also found in Holocene sediments from Buenos Aires, Argentina (Prieto & Quattrocchio 1993).…”
Section: Palynological Analysismentioning
confidence: 99%
“…Relationships between plant spores registered in this work and the present-day taxa occurrence in plant communities at "Jurubatiba Coastal Woodlands National Park" (Rio de Janeiro State). References: Santos & Sylvestre (2001) and Santos et al (2004). (Garcia 1997), in mesophilous woodland at 1500 m a.s.l., in the Sierra Madre Central, Mexico (Gomez-Noguez et al 2013).…”
Section: Palynological Analysismentioning
confidence: 99%
“…A Restinga é uma das fitofisionomias que mais tem sofrido com a devastação nas regiões litorâneas e estudos têm mostrado sua fragilidade frente à ação antrópica e alterações climáticas (Araújo & Maciel 1998, Rocha et al 2007). Sua vegetação esta situada em áreas privilegiados do litoral, sendo constantemente ameaçada pela especulação imobiliária e industrial (Santos et al 2004). Esta região possui características e funções ecológicas únicas que fazem deste ecossistema uma zona de transição e de comunicação entre outros ecossistemas da Mata Atlântica.…”
Section: Agradecimentosunclassified